Teaching Japanese Culture: Timeless Influences - EAA Editorial Office (Education About Asia, 2021)
At the most fundamental level, no humans have created cultures that are completely unique in human history. That said, indigenous practices, interactions with other cultures, and subsequent creative cultural adaptations help to richly enhance any culture. Each one of the following archived EAA articles, intended for teachers and students, are illustrative of cultural practices and influences that remain “timeless” in influencing many Japanese.
Keywords: China; Culture; East Asia; Education; History; Japan; Japanese Language